Throw - Haghighatgou, Fatima (Iran, 2017)
This documentary is about Mohammad Khalvandi (born 11 January 1990). He is an Iranian athlete who competes in disability athletics in the F58 category. At the 2012 Paralympics, Khalvandi set a World Record for the F58 class with a throw of 50.98m as he won gold in the combined F57/58 category and also won the combined F57/58 javelin 2013 World title.
Verzio Film Festival Submission
Keywords: Documentary films